Search for dark matter with the LUX–ZEPLIN detector – acoustic sensor performance and detector response - Carels, C (2018)
The LUX-ZEPLIN experiment needs acoustic sensors to monitor the liquid xenon contained in its time projection chamber (TPC) for irregularities that could spoil a stable liquid xenon environment that is required for a dark matter search. I have developed and implemented algorithms that distinguish the occurrence of bubbling and other sounds, and I have carried out tests using a PVDF sensor and a readout system developed at Oxford; demonstrating that the hardware and analysis meet the requirements for their purpose in LUX-ZEPLIN. Acoustic sensors can be used as a veto to strengthen the fidelity of detector data. The primary event data in LUX-ZEPLIN will come from arrays of photomultiplier tubes, which detect light emitted from recoil events in the TPC. Waveform data from TPC events will be collected through a bespoke data acquisition system. A simulation of the detector response is needed in order to ensure that reliable event analysis will be possible when the experiment starts taking data. I have constructed an analytical model of the full signal chain from the photomultiplier tubes to the digitisers, including all analogue front-end electronics and interconnecting cabling, and I created a Monte Carlo simulation software package in which I have embedded this model. I have used the model and the software to carry out simulations to evaluate the design of the LUXZEPLIN electronics readout system. The model and the simulation I have created play a central role in performing event analysis on simulated data in preparation for real data taking with the LUX-ZEPLIN experiment.